Autophagy Dysregulation in ALS: When Protein Aggregates Get Out of Hand - Ramesh, Nandini; Pandey, Udai Bhan (Frontiers in Molecular Neuroscience, 2017)
Amyotrophic lateral sclerosis (ALS) is a neurodegenerative disorder that results from the loss of upper and lower motor neurons. One of the key pathological hallmarks in the disease neurons is the mislocalization of disease-associated protein accompanied by the formation of cytoplasmic aggregates of disease proteins as well as interacting proteins due to defective protein quality control. This apparent imbalance in the cellular protein homeostasis could be a crucial factor that causes motor neuron death in the later stages of life in patients. Autophagy is a major protein degradation pathway that is involved in the clearance of protein aggregates and damaged organelles. Abnormalities in autophagy have been observed in numerous neurodegenerative disorders, including ALS. In this review, we discuss the contribution of autophagy dysfunction in various in vitro and in vivo models of ALS. Furthermore, we look closely at the cross-talk between autophagy and other cellular stresses implicated in ALS pathogenesis and the therapeutic implications of regulating autophagy in ALS.